1989
DOI: 10.1111/j.2044-8341.1989.tb02831.x
|View full text |Cite
|
Sign up to set email alerts
|

Type A behaviour pattern: Specific coronary risk factor or general disease‐prone condition?*

Abstract: While the association between Type A behaviour pattern and coronary heart disease (CHD) has been abundantly investigated, the question of the specificity of this association remains virtually unexplored. The present study addressed this question by examining, in a sample of 1949 male and female adults, the relationship between JAS Type A measurement and self-reported diseases (i.e. CHD, scarlatina, rheumatoid arthritis, asthma, diseases of the liver, diseases of the gall-bladder, thyroid troubles, tuberculosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 21 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…, Haynes & Feinleib ), its relations with other chronic diseases, such as asthma, liver diseases, tuberculosis, and kidney disease, have been explored (Rime et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…, Haynes & Feinleib ), its relations with other chronic diseases, such as asthma, liver diseases, tuberculosis, and kidney disease, have been explored (Rime et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…The Type A behaviour pattern, manifested as extreme achievement striving, competitiveness, time urgency, hostility and hard driving behaviour has long been associated with the risk of coronary heart disease (Rosenman et al 1975;Haynes et al 1980;Manuck et al 1986), although recent research suggests that specific components may be more harmful than the overall behaviour pattern (Booth-Kewley & Friedman, 1987;Dembroski & Costa, 1987). There is also some evidence that Type A behaviour may be linked with a range of other physical illnesses (Rime et al 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Many authors have investigated the personality characteristics of tubercular patients [130][131][132][133][134] with partially discordant results. The study of Sparer [ 133] showed, for example, that infection was more frequent in depressed personalities, and Dumarest [135] also maintained that, in his clinical experi- ence, 'les joyeux guérissent toujours'.…”
Section: Tuberculosismentioning
confidence: 99%